(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
An experiment was carried out in pot culture to assess the effect of integrated vermicompost and chemical fertilizers on soil physical and chemical attributes, sesame plant growth, seed yield, and nutrient concentrations in agricultural soil. Eleven treatments were arranged in a completely randomized design (CRD) with three replications together with the control. All the vegetative growth and yield promoting attributes viz. plant height (116.20 cm), leaf number (100 plant-1), leaf area (29.34 cm2), pod no. (100 plant-1), and seed no. (64 pod-1), and 1000 seeds weight (3.82g) was highest in T10 containing 15 t ha-1 vermicompost plus 70% RDF (N21P11K14S5 kg ha-1). The control (T1) displayed minimum yield performance and quality characteristics. The total N, P, K, S, Fe, and Zn concentrations and protein content in seeds were measured highest in T10. This study revealed that combining vermicompost with inorganic fertilizer can improve sesame plant growth and seed nutrient content and is recommended for sesame production. J. Asiat. Soc. Bangladesh, Sci. 49(1): 43-53, June 2023